Climate Competitive Industries : A Practitioner’s Handbook - World Bank Group (World Bank, Washington, DC, 2017)
Climate variability and resource scarcity pose an increasing threat to the growth and competitiveness of industry, and nowhere is this issue more significant than in the world’s emerging economies. Governments and industry must work together to tackle this challenge. The World Bank Group’s Climate Competitive Industries (CCI) initiative aims to assist client governments to improve the competitiveness of their manufacturing industry, by facilitating the adoption of cleaner technologies and more efficient practices, tailored to the needs of the private sector. This Guide is designed to provide practitioners with an understanding of the CCI initiative and step-by-step guidance on how to design, develop, and implement a CCI or equivalent program. This book has four modules. Module one provides an overview of the impetus for global action on resource efficiency and the pressures on and the roles of individual enterprises and governments in responding to the challenges and opportunities presented. This Module also provides an introduction to the World Bank Group’s CCI initiative introduces the challenges of climate change and the global pressures on natural resources. Module two provides guidance on how to take an initial concept for an industrial resource efficiency program through to the design stage. It provides the tools to enhance the practitioner’s understanding of a country’s manufacturing base, including the main actors, opportunities, drivers, barriers and success factors. Module three provides guidance on how to implement a resource efficiency program within industry. It provides information on how to raise awareness and work with the core stakeholders throughout the process. Module four focuses specifically on the development of Standards and Labelling (S and L) initiatives.